Occurrence, toxicity and risk assessment of plastic additives in Besos river, Spain. (January 2021) - Bolívar-Subirats, Gabino; Rivetti, Claudia; Cortina-Puig, Montserrat; Barata, Carlos; Lacorte, Sílvia
Abstract: The objective of the present study is to evaluate the presence, seasonal variability and impact of plastic additives along the Besos river basin (Catalonia, Spain). This river flows through a highly urbanized and industrialized area with discharge of >25 Wastewater Treatment Plants (WWTPs) and with large amounts of floating plastics. Compounds studied included 5 phthalates, its substitutes acetyl tributyl citrate (ATBC) and bis(2-ehtylhexyl) adipate, 12 long and short chain alkylphenols, bisphenol A and benzophenone, most of them high volume production chemicals. High-performance liquid chromatography-tandem mass spectrometry (HPLC-MS) was used to determine ng/L concentrations. Toxicity evaluation was performed for each individual compound using Daphnia magna as test organism and it was found that the effect concentration (EC50 ) decreased with increasing octanol-water partition coefficients. The EC50 values calculated and Measured Environmental Concentrations were used to determine the risk quotients. Only diethylhexylphthalate, nonylphenol and octylphenol, with median concentrations from 41.9 to 826 ng/L, caused a small risk mostly in downstream waters with 50–75% of the samples overpassing the Environmental Quality Standards set by the European Union. Seasonal variations were observed with higher levels in summer due to low water flows. WWTPs effluents and leaching from floating plastics or microplastics were presumably main sources of pollution. Highlights: Plastic additives are mostly High Volume Chemicals which are ubiquitous in river water. The toxicity of plasticizers was evaluated using Daphnia magna as model organism. Measured concentrations of DEHP, NP and OP in Besos river produced a risk for aquatic organisms. The source of plasticizes are sewage effluents and leaching from plastics or microplastics.